Strategies To Increase Entrepreneurial Motivation Through Smart Concepts And Financial Planning In The Pesantren Environment: Strategi Meningkatkan Motivasi Kewirausahaan Melalui Konsep Smart Dan Perencanaan Keuangan Di Lingkungan Pondok Pesantren - Avianti, Widiya; Maulana, Dede Yusuf; Izzati, Nur (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Training conducted by a team of Lecturers for two days, as a Community Service activity as a fulfillment of Tridharma elements. Training to increase entrepreneurial motivation by providing the right material, namely the SMART concept as a motivation in shaping entrepreneurial character and financial planning strategies for beginners with the ability to compile KAS journals, is needed by students as a scientific provision to encourage the desire to become santripreuneur. Participants understand the forms of business that can be implemented along with the types of businesses that need to be avoided. Preparation of “Cash Flow” is one of the important processes in managing business finances so that it can be sustainable. The implementation of this training begins with a Pre-test consisting of six question elements and ends with the implementation of the Post-test training results evaluation of six question elements with different compositions. The evaluation results stated that as much as 85% there was an increase in the ability to learn the concept of SMART entrepreneurship and 70% achieved understanding of financial preparation for beginners, so this activity is in accordance with the aim of increasing entrepreneurial skills and on target is expected to form entrepreneurial character